PREPARASI SEL SURYA TERSENSITISASI DYE (DSSC) DARI EKSTRAK KULIT UBI JALAR UNGU (Ipomoea batatas L.) - Aisyah, Aisyah; Jusnia, Jusnia; Nur, Arfiani; Abubakar, A. Nurfitriani; Ibrahim Patunrengi, Iswadi (Teknosains: Media Informasi Sains dan Teknologi, 2023)
Various dyes have been investigated for Dye-Sensitized Solar Cell application. The ethanol extract from peels of purple sweet potato Ipomoea batatas L. is commonly used as a dye in TiO2 semiconductors. However, in this study the dyes were extracted stepwise by three solvents with graded polarity; n-hexane, ethyl acetate, and methanol. Each extract and the mixture are used as the sensitizers for DSSC. This aimed to compare the efficiency value to obtain the highest solar energy conversion into electricity. The DSSC performance was studied based on the phytochemical analysis, UV-Vis and FTIR spectrum, and the semiconductor morphology by SEM analysis. The mixed extract produced the highest cell efficiency of 0,10 with Vmax and Imax values of 276 mV and 25,7 mA, respectively.